Influence of Environmental Factors on the Structure of Soil Microfungi of Vietnamese Tropical Forests - Alexandrova, A. V.; Aldobaeva, I. I.; Kalashnikova, K. A.; Kuznetsov, A. N. (Contemporary problems of ecology, 2018)
Results of a multiyear complex study of species diversity, features and patterns of distribution, substrate colonization, and ecology of soil microscopic fungi in the lowland, piedmont, and mountain monsoon rain forests of Vietnam are presented for the first time. In 97 forest habitats studied within 13 specially protected areas of Vietnam in the Northern, Central, and Southern parts of the country, 510 species of micromycetes from 148 genera have been identified. The influence of environmental factors (climatic features, relief, soils, forest types, etc.) on the formation of complexes of micromycetes has been analyzed. As a result, the dependence of the number of colony-forming units (CFUs) on the type of the substrate and the season (wet/dry) is established: significantly more species are detected in the dry season (October–March) ( p < 0.05) in comparison with the wet one; many species are associated with certain plant species. Indicators of species diversity decrease with an increase above sea level altitude ( p < 0.01). Herewith, the ratio of the taxonomic groups of micromycetes also consistently changes. A latitudinal–zonal trend of the change of the species composition of microscopic fungi, determined by a combination of environmental factors, has been revealed.